NPM1 is a Novel Therapeutic Target and Prognostic Biomarker for Ewing Sarcoma - Zhou, Yangfan; Fang, Yuan; Zhou, Junjie; Liu, Yulian; Wu, Shusheng; Xu, Bin (Frontiers in Genetics, 2021)
Ewing sarcoma (ES) is a cancer that may originate from stem mesenchymal or neural crest cells and is highly prevalent in children and adolescents. In recent years, targeted therapies against immune-related genes have shown good efficacy in a variety of cancers. However, effective targets for immunotherapy in ES are yet to be developed. In our study, we first identified the immune-associated differential hub gene NPM1 by bioinformatics methods as a differentially expressed gene, and then validated it using real time-PCR and western blotting, and found that this gene is not only closely related to the immune infiltration in ES, but also can affect the proliferation and apoptosis of ES cells, and is closely related to the survival of patients. The results of our bioinformatic analysis showed that NPM1 can be a hub gene in ES and an immunotherapeutic target to reactivate immune infiltration in patients with ES. In addition, treatment with NPM1 promoted apoptosis and inhibited the proliferation of ES cells. The NPM1 inhibitor NSC348884 can induce apoptosis of ES cells in a dose-dependent manner and is expected to be a potential therapeutic agent for ES.